Alloy Zr1Nb based on magnesium-thermal zirconium - Lavrinenko, S.D.; Pylypenko, M.M; Drobyshevskaya, A.A.; Bobrov, Yu.P.; Stadnik, Yu.S.; Tantsyura, I.G (Вопросы атомной науки и техники, 2016)
Refining processes of magnesium-thermal zirconium sponge by methods of electron beam and vacuum arc melting in laboratory conditions were investigated. Properties of obtained test samples of zirconium were studied. The works on optimization of melting of alloy Zr1Nb based on magnesium-thermal zirconium domestic production were made. Complex of research works on studying the properties of alloy ingots was made. Structure, chemical composition, thermal desorption, hardness and microhardness of samples of alloy Zr1Nb obtained by electron beam melting and vacuum arc melting under different conditions were investigated and compared.